The virtual customer: a new paradigm for improving customer relations in libraries and information services - K. G. Saur, Sueli Mara Soares Pinto Ferreira RÃ©jean Savard (ifla, 2005)
ix Preface For several years now, the concept of â€œvirtual clientâ€ or â€œvirtual customerâ€ has been part of the world of libraries and information services. Librarians indeed have tamed the computer for a long time now, and what we find in libraries are now third and even fourth generationâ€™s systems. Internet is also part of the environment of libraries for many years, at least in many countries. It seems like what we call the hybrid character of libraries â€“ that is the obligation to manage at the same time virtual and traditional collections and services â€“ has fit in little by little with librariansâ€™ mentalities. And for many specialists, this hybrid library will last still for many many years. Of course we should not forget that the printed document and the person-to-person service on which is built the excellent reputation of libraries, but it is important to look more and more at the virtual side of the library. This phenomenon of the virtual client has not been studied very often in the last years although it is deeply affecting our way of managing and marketing libraries: approaching a customer and satisfying him or her at a distance is commanding challenges much more different than what we find with the traditional model. Just the evaluation of the distant userâ€™s needs, not speaking about the non-user needs, requires special skills. A colloquium on these topics was therefore particularly appropriate. Thus we should thank the Management and Marketing Section standing committee members for having supported this meeting from the beginning as well as IFLA itself for authorizing its venue during summer 2004. The warm welcome from the Brazilian professional community and from the Sao Paulo colleagues must also be underlined: during those few days, the participants were simply cherished! x The colloquium was an important success. All will agree on that. And it was such certainly and mainly because of the authors and their papers which we are publishing here. Without the authors no colloquium of course, and we would like to express them our profound recognition. They have brilliantly tackled the very important issues related to the virtual customer: from more generic points of views such as the democratization of access to digital information to more specific questions such as virtual libraries and new services, not forgetting user and librarian education, web site design, more specialized information, etc. In short, the readers of these proceedings will find along these pages a very stimulating content which we hope, will guide them towards better services for virtual clients. We must also stress the multilingual aspect of this publication: if the colloquium was so interesting, it is also because it was the meeting place of various professional experiences coming from many different countries and expressed in four different languages: Portuguese, Spanish, French and English. It is important for an international association such as IFLA to maintain this multilinguism and the papers are presented here in their original language, with abstracts in the four official languages of the colloquium. This is resulting from a fantastic teamwork and we would like to thank again all those who have contributed to this publication.